Stock Fundamental Analysis and Investment Decision Making - Dwitayanti, Yevi; Juliadi, Ertawan; Dewi, A.Ratna Sari (Westscience Press, 2023)
This research investigates the relationship between stock fundamental analysis and investment decision-making among investors in the dynamic Indonesian stock market. Utilizing a mixed-methods approach, the study combines quantitative analyses of survey data and financial indicators with qualitative insights from interviews and focus group discussions. The findings reveal a significant prevalence of fundamental analysis among investors, with 75% actively incorporating it into their strategies. Subgroup analysis indicates varying utilization rates among individual retail investors (70%), institutional investors (80%), and analysts (85%). Regression analysis establishes a statistically significant positive correlation (β = 0.25, p < 0.05) between the application of fundamental analysis and investment success, with an adjusted R-squared of 0.48. The study identifies key market factors—regulatory changes, economic indicators, and market volatility—that influence the effectiveness of fundamental analysis. The qualitative analysis underscores nuanced investor perceptions and behavioral factors, contributing depth and context to the quantitative correlations. The integrated findings offer valuable insights for investors and policymakers, suggesting implications for informed decision-making and regulatory considerations in the Indonesian stock market.